Performance appraisals strategies for success - Arthur, Diane (American Management Association, 2008)
Learn how to make the performance appraisal process deliver maximum value to the organization. Performance appraisals are a critical tool for aligning employee performance with the goals of the organization. They also provide a key point of contact between managers and their people. Yet there are few tasks managers dread more. This book will equip you to meet this managerial challenge with confidence and enthusiasm. Learn how you can make the performance appraisal process deliver maximum value to both the organization and employees. Assessments, diagrams and checklists help you gain a thorough.